1988
DOI: 10.2105/ajph.78.9.1218
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with OSHA record-keeping requirements.

Abstract: The Occupational Safety and Health Act of 1970 requires employers to maintain records of workplace injuries and illnesses. To assess compliance with the law, data from the National Occupational Exposure Survey (NOES) were examined. Ofthe 4,185 companies with 11 or more employees, 75 per cent maintained OSHA Form 200 designed for recording illnesses and injuries. The number ofemployees and the presence of a union were positive determinants in the record maintenance. Of companies with 500 or more employees, 95 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 1 publication
0
21
0
Order By: Relevance
“…Research indicates that companies with fewer than 100 employees are more likely to inadequately maintain OSHA injury and illness records. Seligman and colleagues 28 found that only 60% of companies employing between 10 to 99 employees maintained OSHA log files for injuries and illnesses. Approximately 50% of the companies in the US employ fewer than 100 employees.…”
Section: Underreporting By Employersmentioning
confidence: 99%
“…Research indicates that companies with fewer than 100 employees are more likely to inadequately maintain OSHA injury and illness records. Seligman and colleagues 28 found that only 60% of companies employing between 10 to 99 employees maintained OSHA log files for injuries and illnesses. Approximately 50% of the companies in the US employ fewer than 100 employees.…”
Section: Underreporting By Employersmentioning
confidence: 99%
“…15,16 Small firms (fewer than 11 employees) are more likely than medium and large firms to be newly formed and frequently go out of business. 17 New owners might not be aware of the law.…”
Section: Causes Of Under-and Overreporting Among Firms Covered By Thementioning
confidence: 99%
“…First, Seligman et al 15 found that OSHA recordkeeping was the worst for small firms and the best for large firms. Second, the BLS Annual Survey data indicate that small firms have among the lowest reported injury rates of all firms.…”
Section: Empiric Evidence On Inaccurate Reportingmentioning
confidence: 99%
“…Leigh, Marcin, and Miller (2004) review many studies that indicate that the BLS survey substantially undercounts nonfatal injuries, perhaps by 40 percent for the sectors covered, and that "Evidence suggests that small firms are especially prone to underreport." Seligman et al (1988) reported that compliance with OSHA recordkeeping requirements was poorest at small firms and best at the largest ones. Glanzer et al's (1998) study of a large construction project found that underreporting was lower for injuries that involved lost workdays than for injuries without lost workdays.…”
Section: Underreporting and Sizementioning
confidence: 99%